2012
DOI: 10.1007/s00125-012-2723-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of autoimmune diabetes in NOD mice by Toll-like receptor 2 tolerance in conjunction with dipeptidyl peptidase 4 inhibition

Abstract: Aims/hypothesis We have shown that chronic administration of the Toll-like receptor 2 (TLR2) agonist Pam3CSK 4 prevents diabetes in NOD mice by inducing TLR2 tolerance of dendritic cells (DCs). We have also reported that a novel dipeptidyl peptidase 4 (DPP4) inhibitor, DA-1229, could increase beta cell mass. Here we investigated whether a combination of DPP4 inhibition, with beneficial effects on beta cell mass, and TLR2 tolerisation, protecting beta cells from autoimmune destruction, could treat a model of es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Prior reports have indicated that treatment with TLR ligands or TNFα could induce a suppressor phenotype in DC [39, 4650]. Here, 1Z1 treated DC exhibited a semi-mature phenotype as indicated by surface activation markers including CD40, MHC class II, CD80 and CD86.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Prior reports have indicated that treatment with TLR ligands or TNFα could induce a suppressor phenotype in DC [39, 4650]. Here, 1Z1 treated DC exhibited a semi-mature phenotype as indicated by surface activation markers including CD40, MHC class II, CD80 and CD86.…”
Section: Discussionmentioning
confidence: 61%
“…DC exposure to a TLR2 ligand enhanced CD4 + CD25 + Treg proliferation, and treatment of pre-diabetic mice with a synthetic TLR2 agonist diminished the onset of T1D, and increased the number and function of CD4 + CD25 + Treg [30, 38, 39]. Hence, involvement of Treg in the anti-inflammatory effect induced by 1Z1 in the NOD mice was studied to address whether 1Z1 directly stimulates Treg,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These PRRs include Toll-like receptors (TLRs) and nucleotide-binding oligomerization domain-like receptors (NOD-like receptors, NLRs). Interestingly, TLR deficiencies on the Non-Obese Diabetic (NOD) mouse background both increase susceptibility to and protect from T1DM [8][9][10][11][12][13]. Deficiency in MyD88, an adaptor protein that mediates most TLR signaling, induced complete protection from T1DM, which was abolished when MyD88 -/-NOD mice were housed in germ-free (GF)…”
Section: Introductionmentioning
confidence: 99%